Green synthesis of silver nanoparticles and degradation of AZO-dyes using Cestrum diurnum plant extract, and antimicrobial activities of AgNP’s. - Kamil Ahmad; Budi Warsito; Jafron Wasiq; Saqib Khan; Naseer Ahmed; Eagu John Calvin; Maria Ashraf (BIORE Scientia Publisher, 2023)
Nanoparticles play an important role now days in different fields like drug delivery, diagnostics, therapy, engineering, energy, healthcare and Environment. The goal of this study was to synthesize Silver Nanoparticles from extract of C. dirnum plant, degradation of azo-dyes with synthesized AgNP’s and finding bioactivity of AgNP’s against bacteria’s. The UV-Visible analysis of solution after addition of AgNP’s showed that the addition of silver NP’s reduced the absorbance peak of methyl orange from 2.87 to 1.0 and absorbance peak of methyl red decreased from 2.92 to 1.75. Green synthesis concepts can be used to create metal nano-particles, which have a promising future in the Azo-dye breakdown process. C. diurnum leaf extract acts as a reducing agent to synthesize metal nano-particles, providing environmentally friendly and energy-efficient alternatives. Bioactivity of AgNP's against gram negative and gram-positive bacteria were tested which gave strong inhibition against bacteria.